Exotic structures on quotient spaces of S3-actions - L. Astey; E. Micha; G. Pastor (International Journal of Mathematics and Mathematical Sciences)
A correct version of some results by A. Rigas regarding S3 actions on S7×S3 and on the symplectic group Sp2 with quotients exotic seven-spheres is presented.